Gompertz Kinetics of Soil Microbial Biomass in Response to Lignin Reinforcing of Urea-Crosslinked Starch Films. (2016) - Majeed, Zahid; Mansor, Nurlidia; ismail, Shaja; Mathialagan, Ranitha; Man, Zakaria
Abstract: Soil microbial biomass (SMB) is strictly a function of substrate quality and composition under the soil environmental conditions. The current research objective was to determine the gompertz kinetics of SMB in response of predictive variables; 5, 10, 15 and 20% lignin, used to reinforce the urea-crosslinked starch (UcS) films in aerobic soil. Through gompertz kinetics, the specific growth rate ( μ max ), lag phase (λ), asymptote ( A ) and inflection ( t i ) of growth curve were determined for SMB. The results of the study showed that gompertz kinetic predicted reasonably a good agreement between the experimental and predicted soil microbial biomass ( R 2 > 0.942; Error Mean Square, 0.010-0.089) for all lignin reinforced UcS films in aerobic soil. The value of A was 13.39% higher in soil added with lignin reinforced UcS films than the control film. The average μ max of lignin reinforced UcS films was achieved 3.59 day -1 which was approximately 9.10% less than μ max observed in control film. The average λ was delayed 76.69% more in lignin reinforced UcS films possible due to the lignin's recalcitrant nature to biodegradation by microorganisms. The t i was found 39.53% higher for the lignin reinforced UcS films. The higher oxidation state and higher standard enthalpy of combustion of the UcS increase by addition of the lignin which could cause the higher carbon to microbial biomass conversion. These results predicted by gompertz kinetics have demonstrated the implication of lignin to use in biopolymer films of low enthalpy of combustion (starch) in order to increase the carbon conversion into the microbial biomass rather than rapid conversion into the CO2 .